2023
DOI: 10.29333/ejgm/12602
|View full text |Cite
|
Sign up to set email alerts
|

Psychological health outcome of Sub-Saharan African migrants in Germany

Abstract: African migrants living in Europe have an increased risk of adverse psychological health outcomes compared to people without a migration background. The increased vulnerability may be due to their migration experience and possible challenges in adapting and integrating into the host community. This study explores the association between community solidarity and psychological health outcome among Sub-Saharan African (SSA) migrants in Germany.<br /> The study used data from 518 SSA migrants in Germany coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 48 publications
(46 reference statements)
0
5
0
Order By: Relevance
“…Although displaced persons constantly worry about their socioeconomic disadvantages, their sense of community can be seen in their solidarity, which is one attribute they have developed. Solidarity allows them to adapt and promote their psychological health, emotional, cognitive, behavioral, and social well-being [ 28 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Although displaced persons constantly worry about their socioeconomic disadvantages, their sense of community can be seen in their solidarity, which is one attribute they have developed. Solidarity allows them to adapt and promote their psychological health, emotional, cognitive, behavioral, and social well-being [ 28 , 56 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various socio-demographic characteristics assessed as control variables were sex (male and female), age (20–25, 26–30, 31–35, 36–40, and >40), and education (none, primary, secondary and tertiary) and marital status (married, single, widowed, and divorced) were also explored. Socio-demographic variables were controlled for because several studies have indicated that these factors influence the formation of social networks [ 28 , 29 , 69 ]. By controlling for these socio-demographic variables, all forms of bias resulting from the different characteristics of the recruited displaced persons are controlled.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations